Uma avaliação do conceito de regência e transitividade na tradição gramatical do português - Neves, Maria Helena de Moura [UNESP] (GN1 Sistemas e Publicacoes, 2014)
In this paper, we study patterns of complementation as well as transitivity in Portuguese grammatical tradition aiming at verifying the motor of interest toward these subjects as well as eventual historic changes in the direction of the treatment they have been given. We analyze the concepts, the relations and the grounding notions in this camp, as well as the (in)transitive property of verbs in correlation with the status of their complements. Historically documented normative determinations of the notion of complementation and the modern reactions to such a view are relevant to our examination. Our conclusion moves toward a socio‑historic conditioning of traditional lessons, acknowledging, however, the natural existence of theoretical directions in the proposals.

Estuda-se regência e transitividade na tradição gramatical do português, com o objetivo de verificar os móveis do interesse pelo tema, bem como alguma eventual mudança histórica de direção no modo do tratamento proposto. Analisam-se a conceituação, as relações e as noções de base nesse campo, bem como a visão da propriedade (in)transitiva dos verbos, em correlação com a do estatuto dos complementos. Têm relevância a determinação normativa historicamente documentada da noção de regência e a reação moderna a esse modo de ver. Conclui-se por um condicionamento histórico-social das lições tradicionais, reconhecendo‑se, porém, a natural existência de uma direção teórica nas propostas.
An evaluation of the concept of patterns of complementation and transitivity in Portuguese grammatical tradition
Keywords: Patterns of complementation; Transitivity; Traditional grammar; Regência; Transitividade; Gramática tradicional